Clinical drug development for dementia with Lewy bodies: past and present. (2nd November 2019) - Lee, Garam; Cummings, Jeffrey; Decourt, Boris; Leverenz, James B.; Sabbagh, Marwan N.
ABSTRACT: Introduction : Dementia with Lewy bodies (DLB) is an under-researched area despite being the second most common type of degenerative dementia after Alzheimer's disease. It is an area of unmet need with no approved symptomatic or disease-modifying therapies. The pharmacological management of DLB is complex and challenging because early trials of drugs for DLB have resulted in no demonstrable efficacy. Randomized controlled trials (RCTs) in the DLB population have only recently been initiated. Understanding results from previous and current clinical trials in DLB can provide insights for future research and development. Areas covered : We provide an overview of the DLB drug development landscape and the current treatment strategies. We reviewed ClinicalTrials.gov to identify all clinical trials for the treatment of DLB. Expert opinion : DLB drug development has significantly improved in recent years with eight agents now in clinical trials. However, more rigorous RCTs are urgently needed. Diagnostic criteria must be optimized to accurately diagnose patients for clinical trials and care. New biomarker strategies are necessary to improve diagnostic capabilities and trial designs, and novel drug targets should be identified to develop DLB specific disease-modifying therapies. Evaluating the current drug development landscape can provide insight into how best to optimize development practices.